Examination of the Relationship Between Quality of Life and Leisure Satisfaction by Canonical Correlation Analysis - Tennur Yerlisu Lapa; Elif Köse; Evren Tercan Kaas (Pamukkale University, 2023)
Leisure activities are one of the determinants of quality of life, among others. In this context, this study focuses on all dimensions of satisfaction from leisure activities and quality of life. Canonical correlation analysis was used, and 300 university students were included in the study via convenience sampling method. Data collection tools of the research of "Satisfaction with Life Scale" and "Short-Form-36 Health Survey". According to the research findings, the shared variance between the quality of life and leisure satisfaction data sets was 31.955% for the first canonical function and 19.270% for the second canonical function. In the first canonical function, the physical function variable from the life quality data set and psychological, education, social, and physiologic variables from the leisure satisfaction data set had a relationship in the same direction. In the second canonical function, physical role and emotional functions from the quality of life and relaxation from leisure satisfaction data set had a relationship in the same direction. Leisure satisfaction could be expressed to increase the quality of life in university students. The results indicated that increasing the opportunities for university students to join leisure activities would give beneficial results.